HUBUNGAN DUKUNGAN KELUARGA DENGAN AKTIVITAS FISIK PADA LANSIA DENGAN HIPERTENSI - Diana Helda; Ludia Seprianti (Jurnal Kesehatan dan Pembangunan, 2022)
Aging is the process of slowly losing the ability of tissues to repair themselves. One of the health problems experienced by the elderly is hypertension. If hypertension is not treated, it can affect the body's system. Purpose of the study: To determine the relationship between family support and physical activity in the elderly with hypertension. Method : The design used is a quantitative non-experimental design. The number of respondents was 20 people. Based on the results of the study: From the statistical test results p value 0.032 < 0.05, then Ha is accepted, meaning that there is a relationship between family support and physical activity in the elderly with hypertension. Conclusion: Based on the results of research that has been carried out on 20 elderly respondents at the Kenten Palembang Health Center in 2021 using primary data in the form of questionnaires and checklists, there is a relationship between family support and physical activity in the elderly with hypertension. Suggestion: It is hoped that the results of this study can be input for the Kenten Palembang Public Health Center to provide counseling to families who have the elderly so that they can provide emotional support, appreciation, instrumental and information well, including paying attention to physical activities that are not burdensome for the elderly.